Self-perceived far vision quality and night driving difficulties are not related to night myopia or visual acuity - Andrés Gené-Sampedro; Javier Gene-Morales; Francisco Alonso; Susana Montecelo Salvado; Sergio A. Useche (PLoS ONE, 2026)
This study aimed to psychometrically validate the Night Drive Questionnaire (NDQ), a new tool designed to assess self-reported far vision quality and difficulties related to night driving. Additionally, we evaluated the questionnaire’s potential for detecting and characterizing night myopia at an early stage. A total of 115 drivers, aged between 18 and 63 years (53% female), who regularly drove at night, completed the Night Drive Questionnaire (NDQ). Participants also had their refraction shift (night myopia) and visual acuity shift measured. Both refraction and visual acuity shift were calculated as the difference between the mesopic (low light) and photopic (normal light) measurements. We evaluated the 1) psychometric qualities through exploratory and confirmatory factor analyses, and 2) concurrent validity through correlations (Spearman) between the NDQ factors and night myopia and standard visual acuity shift and comparisons (Welch) between age groups, sexes, and night myopia levels. The NDQ displayed the best psychometric properties with a four-factor adjusted model, which includes: F1 – Quality of Far Vision, F2 – Difficulties in perceiving with central vision, F3 – Difficulties in perceiving with peripheral vision, and F4 – Difficulties in perceiving with the interaction of central and peripheral vision. This model demonstrated acceptable validity, consistency, and reliability indexes. Males compared to females reported fewer difficulties perceiving with central and peripheral vision and the combination of both (all p ≤ 0.011). There were no significant differences in driving difficulties based on age (all p ≥ 0.252) or night myopia groups (all p ≥ 0.242). Additionally, there were non-significant correlations between the factors and either night myopia or visual acuity shift (all p ≥ 0.092). In summary, the results indicate that the NDQ is a valid and reliable tool for measuring self-reported quality of far vision and the visual-related difficulties experienced during night driving, whether related to central, peripheral, or mixed vision. However, it is not effective in detecting or characterizing night myopia. Future studies should assess whether the NDQ is valid for identifying other visual function parameters that are more directly linked to night driving challenges.